Communicative Competence, Self Confidence and Speaking Performance : Correlation Study - Akbar, Lingga Oka; Firdaus, Masagus; Mulyadi, Mulyadi (LPPPI Publishing, 2025)
The aim of the research was to find out the correlation among communicative competence, self-confidence and speaking performance of the tenth grade students at Senior High School PGRI number 2 Palembang.And, the study was focus to find out whether there was a correlation or not among communicative competence, self-confidence, and speaking performance.The research method was quantitative. The population of the study were all the the tenth grade students of Senior High School PGRI Number 2 Palembang. The sample of the study consisted of 144 students. The Method of sampling in this research was random sampling.The technique of collecting data of students’communicative competence by using components of communicative competence test. The technique of collecting data of students’ self-confidence by using questionnaire. The technique of collecting data of speaking test was from students speaking performance. The technique of data analysis used the Pearson product moment correlation.The technique of data analysis used the Pearson product moment correlation.The research findings showed that Fcount was higher than Ftable (15.752>3.28). It means that the correlation among communicative competence, self-confidence and speaking performance was categorized in high correlation.Then it showed that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected, because N.Sig ? 5 % (0.000 ? 0.05). In this case that students communicative competence and self-confidence have correlation and give influence to students’ speaking performance.